Community-Based Tourism Governance: Document Analysis of Palangka Raya Tourism Village Policy - Varel; Apolus Firnandus; Rendy Stalar (Master of Public Administration FISIPOL Universitas Negeri Surabaya, 2026)
This study examines community-based tourism governance in Palangka Raya City through a document analysis of Palangka Raya City Regulation Number 9 of 2024 on Tourism Villages. The research aims to assess the regulation's philosophical and legal foundations, institutional design, community-empowerment provisions, and implementation gaps from the perspectives of collaborative governance and Community-Based Tourism. A qualitative document-analysis approach was employed by systematically reviewing the regulation's articles and comparing them with relevant governance literature and secondary evidence on local tourism management. The findings show that the regulation represents a progressive shift from state-centered tourism administration toward a more collaborative arrangement by assigning facilitative roles to government agencies and providing legal recognition for community-based tourism management organizations. It also requires the preservation of Dayak cultural identity, local environmental values, and ecological sustainability within tourism destinations. Nevertheless, several important policy gaps remain. The regulation does not establish a clear institutional mechanism for conflict resolution, a detailed and equitable revenue-sharing formula, or operational standards for environmental carrying capacity. These limitations may weaken implementation when interests among government, community groups, customary institutions, and private actors diverge. The study concludes that the effectiveness of the regulation depends heavily on a comprehensive Mayoral Regulation that operationalizes collaborative forums, formally integrates customary institutions, establishes visitor carrying-capacity limits, and provides transparent mechanisms for equitable benefit distribution.